Stereotypic animal behaviour : fundamentals and applications to welfare (CABI, 2006)
This book is comprised of 11 chapters generally discussing different perspectives of stereotypic behaviour in man and animals. The chapters are divided into 3 parts (normal animal and abnormal environment, stereotypic behaviours as pathologies and treating stereotypic behaviours). The first chapter reviews the extent and nature of research into stereotypic behaviour. Chapters 2-4 (part I) focus on the ethological perspective. Behaviour is discussed, including stereotypies, in terms of its motivated basis (stereotyping subjects are normal animals responding in species-typical ways to an abnormal environment). Chapters 5-8 (part II) emphasize clinical psychology, psychiatry and neuroscience. Three assumptions are presented: stereotypies of focus are the products of dysfunction (animal is abnormal); fullest understanding of stereotypies will come from investigating the neurophysiological mechanisms involved; and processes involved at this level have great cross-species generality. Part III (chapter 9 and 10) illustrates how stereotypies can be tackled and reduced by those concerned about their unaesthetic appearance and/or welfare implications. Chapter 11 provides a synthesis of the book and future research and suggestions on how terminology can be improved.